Implementation of the Student Employability Journey (STAR) Program for Career Preparation at Telkom University - Lia Marlia; Sari Nurlatifah (Ma'soem University, 2026)
Career preparation programs in higher education must be well-designed and recognized as a strategy for helping students enter the workforce successfully. This article describes the implementation of the Student Employability Journey (STAR) program at Telkom University and analyzes its alignment with internationally recognized career guidance frameworks—namely the Gatsby Benchmarks and the career development competencies established by the National Occupational Information Coordinating Committee (NOICC). This qualitative study used a non-interactive document analysis design, drawing on a data corpus comprising the Strategic Plan of the Directorate of Career Development, Alumni, and Endowment, the management performance contract, STAR implementation reports, program records, and related institutional policies. Data were analyzed through identification, categorization, and synthesis to map program components against the reference frameworks. Findings indicate that STAR is structured around three core stages: pre-career preparation, career preparation, and job immersion, which accommodate the NOICC domains of self-knowledge, educational and occupational exploration, and career planning. The analysis reveals that all eight Gatsby Benchmarks are accommodated within the program's design and implementation, particularly through integrating career-related activities into the learning process, using digital technology, providing career assessment and counseling services, and building industry partnerships. Nevertheless, several aspects require strengthening: data-driven labor market information, integration of career service platforms within existing systems, and measurement of the program's impact on student and graduate work readiness. These findings suggest that STAR can serve as a structured model for career preparation programs in higher education, while offering a reference point for developing career services grounded in internationally recognized frameworks.